Enhanced thermal degradation of 2, 2′-dichlorodiethyl sulfide (sulfur mustard, HD) with the presence of metal oxides. (2nd August 2016) - Jung, Hyunsook; Lee, Hae Wan; Jeong, Eun Ah
GRAPHICAL ABSTRACT: ABSTRACT: Thermal degradation of sulfur mustard (2, 2′-dichlorodiethyl sulfide, HD) in the presence of metal oxide adsorbents was investigated by thermal desorption in conjunction with gas chromatography–mass spectrometry (GC-MS). Zr(OH)4, Al2 O3, Al2 CoO4, MgO, CeO2, and V2 O5 were used as metal oxide adsorbents. Neat HD was spiked onto the metal oxides packed in glass tubes, which were kept at room temperature and then heated at moderately elevated temperatures of 100°C by a thermal desorption system. The products of thermal degradation were directly transferred and analyzed by GC-MS. 1, 4-Dithiane and 1, 4-oxathiane were characterized as the major products of the thermal degradation of HD in the presence of Zr(OH)4, Al2 O3, Al2 CoO4, and CeO2 adsorbents. No effective degradation was observed with MgO and V2 O5 . Of particular note is Zr(OH)4, which extremely enhanced the thermal degradation of HD.